The Spatial Distribution of Liquefaction Susceptibility by Logistic Regression Model Adapted for Adapazari, Turkey - MERT, AHMET CAN; AREL, ERSİN; ÖNALP, AKIN (My University, 2020)
A logistic regression model has been developed for evaluation of soil liquefaction by the use of cone penetration test (CPTu, PCPT) on data collected from Adapazari, Turkey. The model inputs are the clean sand equivalent normalized cone tip resistance (q(c1N,cs)) and cyclic stress ratio corrected for moment magnitude of 7.5 earthquake (CSRM=7.5) that was experienced in 1999. Liquefaction probabilities (P-L) are obtained for each district of the city for which CPTu data is available with the proposed logistic regression model. Average liquefaction probabilities of the depth interval 0-6 m and coordinates (Longitude, Latitude) of CPT soundings were plotted to construct a liquefaction probability map by longitude and latitude. In order to show the effect of depth in liquefaction potential, the obtained liquefaction probability contours were reconstructed by dividing 0-6m depth into three narrow sublayers of 0-2m, 2-4m and 4-6m wherein liquefaction was observed during the earthquake. For each depth interval, liquefaction probabilities of the districts are compared with the observed liquefied and non-liquefied sites in the city after 1999 Adapazari Earthquake.
Keywords: Liquefaction; CPT; Logistic Regression; Probability of Liquefaction